Comparison of Clinical Characteristics and Neuroimaging of Cerebral Palsy with and without Epilepsy in Children - Rizka Yulianti1 , Prastiya Indra Gunawan2, Darto Saharso3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Cerebral palsy (CP) is one of the main causes of limited activity in children. The prevalenceof CP ranges from 2.6 to 2.9 per 1000 live births. Most of children with CP have at least one comorbid,including epilepsy. Epilepsy in CP is difficult to control, and can increase the severity of motor impairmentand cognitive function, therefore the prognosis is poor. The incidence of epilepsy in CP is associated witha specific clinical profile. This study aimed to analyze the comparison of clinical characteristics of cerebralpalsy in children with and without epilepsy.Methods: A cross-sectional study was conducted using medical record of children with cerebral palsy inpediatric neurology outpatient clinic in Dr. Soetomo Hospital Surabaya in March - May 2020. Childrenwith CP who met the inclusion criteria were included in this study. The variables studied included sex,perinatal history (preterm birth, low birth weight, and neonatal asphyxia), neonatal seizures, spastic type,level of GMFCS, head circumference, neuroimaging features, hearing loss, and eye abnormalities. Thestudy subjects were divided into two groups. Group 1 consisted of children with CP and epilepsy. Group 2consisted of children with CP without epilepsy. Data analysis was performed using the Chi-square test andfisher’s exact test using SPSS.Result: Significant comparison of the characteristics were found in the history of neonatal seizures andthe level of GMFCS. The percentage of neonatal seizures was higher in group 1 at 61.3% (p=0.049). Thedegree of GMFCS in group 1 was dominated by GMFCS III while in group 2 it was dominated by GMFCSIV (p=0.047). Subjects with GMFCS I and II levels were only found in group 2, while in group 1 withhigher level of GMFCS, they were GMFCS III, IV, and V. More abnormal neuroimaging was found ingroup 1, namely 64.3%, while in group 2 it was 57.1%. There was no statistically significant difference ofneuroimaging characteristics between the two groups (p= 0.911).Conclusion: There were differences in clinical characteristics associated with neonatal seizures and GMFCSbetween CP with and without epilepsy.